Motivational profiles as a predictor for physical activity during early months of the COVID-19 global pandemic - Moore, Kristen, author; Li, Kaigang, advisor; Graham, Daniel, committee member; Dunton, Genevieve, committee member (Colorado State University. Libraries, 2021)
The COVID-19 Global pandemic resulted in United States officials mandating stay-at-home, shelter in place, and quarantine ordinances starting in March 2020, limiting opportunities for physical activity (PA) during this period. Motivational profiles use controlled and autonomous attributes of motivation to predict PA maintenance; however, the effect of motivational profiles on PA during the COVID-19 pandemic is unknown. Therefore, the current study used Ecological Momentary Assessment (EMA) to examine the relationship between motivational profiles and daily PA during the COVID-19 pandemic. A convenience sample of 481 U.S. adults (Mage=34.9 years, 78.1% female) participated in a 28-day smartphone-based EMA study during the early months of the COVID-19 pandemic (April – June 2020). EMA surveys assessed number of PA bouts (> 10 mins), length of PA bout, and types of PA completed during the day, which was used to calculate daily PA mins and daily PA metabolic equivalent (METs) mins. A baseline online survey assessed motivation for PA, using the Behavioral Regulation for Exercise 3 (BREQ-3) questionnaire, and demographic information. Latent Profile Analysis (LPA) of the BREQ-3 identified motivational profiles for PA. Separate multi-level linear regression models examined motivational profiles as predictors of average daily PA mins and daily PA MET mins as well as interactions of motivational profile x time (i.e., days in the study). Models controlled for age, sex, ethnicity, income, employment status, body mass index, study site, and start date LPA revealed four distinct motivational profiles for PA including: Class 1) High amotivation (n=102, 21.5%), Class 2) Low controlled motivation (n=55, 11.6%), Class 3) High external regulation (n=47, 9.9%), and Class 4) Moderate autonomous motivation (n=271 57.1%). There were significant negative main effects of motivational profile and time on daily PA mins and daily PA MET mins (b= -0.32, p<.001, b= -1.4, p<.001, respectively). Significant interaction effects of class and time were also detected. Class 2 showed greater decreases in daily PA mins (b=-0.31, p<.01) over time than Class 1. Class 2 and Class 4 also showed significantly greater decreases in daily PA MET mins (b=-1.81, p<.05, and b =-1.49, p<.01, respectively) than Class 3. Motivational profiles for PA predicted mean PA engagement and PA engagement over time during early months of the COVID-19 pandemic. Contrary to previous research, more autonomous/less controlled motivational profiles showed the steepest declines in PA over time; whereas, more amotivated/externally regulated motivational profiles reported lesser declines over time. These findings suggest that COVID-19 restrictions for PA participation may have mitigated the influence of autonomous/less controlled motivation on maintaining PA over time among this sample.
Keywords: latent profile analysis; motivational profiles; self-determination theory; motivation; COVID-19; physical activity